Penerapan Model Pembelajaran Jigsaw untuk Meningkatkan Keterampilan Berbicara pada Pembelajaran Bahasa Inggris untuk Pemandu Wisata - Kadek Feni Aryati; I Putu Agus Endra Susanta; Gede Eka Wahyu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
English speaking skills are a crucial competency for tour guides. This ability enables them to communicate effectively with international tourists, provide comprehensive information, and create memorable travel experiences. However, students often experience difficulties in developing their speaking skills. This article discusses the application of the Jigsaw learning model as an alternative to improve English speaking skills for students as prospective tour guides. The Jigsaw model promotes collaboration, positive interdependence, and individual accountability, all of which contribute to the improvement of speaking skills. This study uses a Quasi-experimental method, with a pre-test and post-test control group design. Data collection was carried out through observation of the implementation of communication skills learning tests and questionnaires to find out how students respond to learning. In this study, the research subjects were 60 students from two classes of the Diploma IV Hotel Management program. The results showed that students' communication skills were influenced by the Jigsaw model learning, with a t-test of 0.00. The results of students towards Jigsaw learning reached 75.67%, which indicates that students responded well to the Jigsaw model.